ENHANCING STUDENT ENGAGEMENT, ACADEMIC ACHIEVEMENT, AND BEHAVIOR THROUGH AUTHORITATIVE TEACHING AND DIFFERENTIATED INSTRUCTION IN GRADE 1 ELEMENTARY CLASSROOM - Naila Adhana Dewi; Donald Samuel Slamet Santosa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the influence of authoritative teaching and differentiated instruction on three key student outcomes: student engagement, academic achievement, and student behavior in early primary education settings. The research aimed to identify whether the implementation of a combined teaching strategy—characterized by high expectations, structured guidance, and responsiveness (authoritative teaching), alongside tailored learning approaches (differentiated instruction)—can significantly impact students’ learning experiences and outcomes. A quantitative research design was employed, using a structured questionnaire distributed to Grade 1 teachers at an international school in Bekasi. The study received responses from eight participants. Linear regression analysis was applied to examine the relationship between the independent variable (authoritative teaching and differentiated instruction, abbreviated as AT_DI) and each of the three dependent variables. Findings reveal that AT_DI has a statistically significant and positive influence on academic achievement (R² = 0.7408, p = 0.0129) and student behavior (R² = 0.910, p = 0.0008). These results suggest that when teachers effectively combine authoritative and differentiated approaches, students tend to perform better academically and exhibit more positive classroom behavior. However, the analysis also indicates that the impact of AT_DI on student engagement is minimal and not statistically significant (R² = 0.121, p = 0.444). The findings highlight the importance of a holistic approach in teaching, where instructional methods are not only aligned with curriculum goals but also thoughtfully adapted to accommodate the diverse needs, learning styles, and developmental characteristics of students, ensuring a more inclusive and effective learning environment that promotes active participation, meaningful engagement, and long-term academic growth.